Pengaruh Strategi Pembelajaran Berdiferensiasi Terhadap Hasil Belajar Ditinjau dari Kemampuan Awal Siswa pada Materi Bangun Ruang - Juandi, Juandi (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to investigate the effect of different learning strategies on students' basic abilities. This study used a quantitative experimental design with a single-group pre-test and post-test methodology. This study used a single-group pre-test and post-test design. The pre-test and post-test had 10 multiple-choice questions and 5 essay questions. The data analysis technique used was to conduct a hypothesis test of the N-Gain test. This study was conducted at SMP Negeri 01 Sungai Kakap, including a sample of 28 students from class VIII A. The results of the pre-test post-test normality assessment showed a normal distribution, with a p-value of 0.155, above the significance threshold of 0.05, which was 0.073. The N-Gain result was 0.4614, indicating a substantial gain. The paired sample t-test produced a significance value of 0.000, which was less than 0.005, resulting in the rejection of the null hypothesis (H0). The t-test revealed a substantial impact of different learning approaches on students' learning outcomes in spatial form.